EFFECT OF EGGSHELL FLOUR ON BLOOD CALCIUM LEVELS IN PREGNANT MICE - Ida Ratna Safitri; Supriyana Supriyana; Bahiyatun Bahiyatun (Belitung Raya Foundation, Indonesia, 2017)
Objective: To examine the effect of eggshell flour on blood calcium levels in pregnant mice. Methods: This was a true experimental study with pretest and posttest control group design. The research was conducted at the Nutrition Laboratory of the Center for Food and Nutrition Studies, Gadjah Mada University on December 1, 2017 to December 31, 2017. There were 30 pregnant rats included using simple random sampling, which assigned in five groups. Spectrophotometer was used to measure blood calcium levels. Paired t-test and One-way ANOVA were used for data analysis. Results: There were significant differences in blood calcium levels before and after treatment with eggshell flour dose 5.4 mg/dl (p= 0.000), 10.8mg/dl (p = 0.000), and 21.6 mg/dl (p = 0.000). There was also significant difference in blood calcium levels in control group with generic tablet of calcium powder of 21.6 mg/dl (p = 0.000). Conclusion: There was a significant effect of given eggshell flour for 7 days with dose 5.4 mg/dl, 10.8 mg/dl, and 21.6 mg/l as well as generic tablet of calcium powder of 21.6 mg/dl in increasing blood calcium levels. Thus, eggshell can be used as alternative for calcium supplement.